Residual Adrenal Function in Autoimmune Addison’s Disease—Effect of Dual Therapy With Rituximab and Depot Tetracosactide - Napier, Catherine (J Clin Endocrinol Metab, 2019)
CONTEXT: In autoimmune Addison’s disease (AAD), exogenous glucocorticoid (GC) therapy is an imperfect substitute for physiological GC secretion. Patients on long-term steroid replacement have increased morbidity, reduced life expectancy, and poorer quality of life. OBJECTIVE: The objective of this article is to restore adrenocortical steroidogenic function in recent-onset AAD. DESIGN: An open-label, multicenter trial of immunotherapy and trophic stimulation in new-onset AAD was conducted. Serial measurement of serum and urine corticosteroids at baseline and throughout a 72-week follow-up period was performed. SETTING: This study was conducted at the endocrine departments and clinical research facilities at 5 UK tertiary centers. PATIENTS: Thirteen participants (9 female, 4 male; age 19-64 years) were included with AAD confirmed by high adrenocorticotropin, low circulating cortisol (basal < 100 nmol/L or post-tetracosactide < 300 nmol/L), and positive serum 21-hydroxylase antibodies. INTERVENTION: All participants received dual therapy with B-lymphocyte–depleting immunotherapy (rituximab 1 g given twice) and repeated depot tetracosactide (1 mg on alternate days for 12 weeks). MAIN OUTCOME MEASURE: Restoration of normal GC secretion (stimulated cortisol > 550 nmol/L) at week 48 was the main outcome measure. RESULTS: Ten of 13 (77%) participants had detectable stimulated serum cortisol (26-265 nmol/L) at trial entry. Following intervention, 7 of 13 (54%) had an increase in stimulated cortisol measurement, with a peak response of 325 nmol/L at week 18 in 1 participant. Increased steroid metabolites, assayed by urine gas chromatography–mass spectrometry at week 12 and week 48, was detected in 8 of 13 (62%) individuals, reflecting an increase in endogenous steroidogenesis. Four of 13 had residual adrenal function at 72 weeks. CONCLUSION: Combined treatment with rituximab and depot tetracosactide did not restore normal adrenal function. Nevertheless, adrenocortical plasticity is demonstrated in some patients, and this has the potential to be exploited to improve adrenal function.